Changes in structural and pigmentary colours in response to cold stress in Polyommatus icarus butterflies - Krisztián Kertész (Nature Portfolio, 2017)
Abstract While numerous papers have investigated the effects of thermal stress on the pigmentary colours of butterfly wings, such studies regarding structural colours are mostly lacking, despite the important role they play in sexual communication. To gain insight into the possible differences between the responses of the two kinds of colouration, we investigated the effects of prolonged cold stress (cooling at 5 °C for up to 62 days) on the pupae of Polyommatus icarus butterflies. The wing surfaces coloured by photonic crystal-type nanoarchitectures (dorsal) and by pigments (ventral) showed markedly different behaviours. The ventral wing surfaces exhibited stress responses proportional in magnitude to the duration of cooling and showed the same trend for all individuals, irrespective of their sex. On the dorsal wing surface of the males, with blue structural colouration, a smaller magnitude response was found with much more pronounced individual variations, possibly revealing hidden genetic variations. Despite the typical, pigmented brown colour of the dorsal wing surface of the females, all cooled females exhibited a certain degree of blue colouration. UV-VIS spectroscopy, optical microscopy, and scanning and transmission electron microscopy were used to evaluate the magnitude and character of the changes induced by the prolonged cold stress.